Akuntansi Syariah dan Pengentasan Kemiskinan dalam Menciptakan Kesetaraan Sosial di Indonesia - Vera Diyah Anggriani; Rayyan Firdaus (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
Islamic accounting has developed as a financial method aimed at promoting social justice and people's well-being in addition to making profit. Islamic accounting has a strategic role in reducing poverty and creating social equality in Indonesia, which is the world's largest Muslim population. The study analyzed how the application of islamic accounting based on principles such as transparency, justice, and social responsibility could help reduce poverty rates in Indonesia. Through literature and secondary data analysis, the study found that islamic accounting, mainly by instruments such as zakat, wakaf, and qardhul hasan, could provide financial solutions that support poor people's economic empowerment. Islamic accounting not only serves as a accounting system, but also as a tool to help strengthen the redistribution of wealth and build an inclusive economy.